Morocco : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Morocco. (IMF Staff Country Reports; Country Report ;, 2016)
The 2015 Article IV Consultation discusses key issues related to the economic growth of Morocco. The macroeconomic situation of Morocco continues to improve. Although growth is recovering and should reach 4.7 percent in 2015, nonagricultural activity remains sluggish and inflation remains low. In 2016, growth will be affected by a base effect following the very good 2015 agricultural season, but a gradual recovery is expected in 2017. Although recent policy action and a more favorable external environment have yielded macroeconomic improvements, the reform needs to be maintained to secure longer-term stability and raise growth potential. Much remains to be done to secure higher and more inclusive growth.